2022
DOI: 10.1186/s12933-022-01550-4
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term prognosis of admission hyperglycemia in patients with and without diabetes after acute myocardial infarction: a retrospective cohort study

Abstract: Objective Admission hyperglycemia is associated with poor prognosis in patients with acute myocardial infarction (AMI), but the effects of baseline diabetes status on this association remain elusive. We aim to investigate the impact of admission hyperglycemia on short and long-term outcomes in diabetic and non-diabetic AMI patients. Methods In this retrospective cohort study, 3330 patients with regard to first-time AMI between July 2012 and July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Inflammation promotes the progression of atherosclerosis during clinical stability and triggers instability and acute coronary syndrome. Although hs-CRP is a benchmark biomarker for CHD inflammatory risk, it is possibly a downstream indicator of inflammatory pathway activation rather than a direct causative factor of cardiovascular events. , Furthermore, our study revealed that blood glucose levels in patients with AMI were higher than those in healthy individuals and patients with SAP, possibly as a transient response to ischemic injury, independent of a history of diabetes . Elevation in blood glucose is strongly correlated with the worsening of conditions as hyperglycemia can further disrupt the dynamic balance of endothelial cells, amplify inflammation, and cause a prothrombotic state and ischemic burden .…”
Section: Discussionmentioning
confidence: 68%
“…Inflammation promotes the progression of atherosclerosis during clinical stability and triggers instability and acute coronary syndrome. Although hs-CRP is a benchmark biomarker for CHD inflammatory risk, it is possibly a downstream indicator of inflammatory pathway activation rather than a direct causative factor of cardiovascular events. , Furthermore, our study revealed that blood glucose levels in patients with AMI were higher than those in healthy individuals and patients with SAP, possibly as a transient response to ischemic injury, independent of a history of diabetes . Elevation in blood glucose is strongly correlated with the worsening of conditions as hyperglycemia can further disrupt the dynamic balance of endothelial cells, amplify inflammation, and cause a prothrombotic state and ischemic burden .…”
Section: Discussionmentioning
confidence: 68%
“…An early study in patients after acute MI showed that abdominal obesity may be an independent predictor of all-cause mortality in men and perhaps also in women [30]. Also, hyperglycemia, particularly on admission, has been related to a poor short-term and long-term prognosis in patients with acute MI [31], even in patients without diabetes [32]. In addition, a recent study suggested that dyslipidemia characterized by high triglyceride and low non-HDL cholesterol may be important residual risk factors for the recurrence of MI in patients after acute MI [33].…”
Section: Discussionmentioning
confidence: 99%
“…HF was diagnosed as per the typical symptoms, signs, and laboratory tests, including orthopnea, acute pulmonary edema, and brain natriuretic peptide (BNP) testing. MI was considered as [ 1 ] symptoms of ischemic chest pain; [ 2 ] a characteristic ST-T dynamic evolution on the electrocardiogram, or with abnormal q waves; [ 3 ] serum myocardial enzyme spectrum increased and decreased. Nonfatal MI was diagnosed as new pathological Q waves in ≥ 2 contiguous electrocardiogram leads according to the previous study [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite extensive progress in the field of interventional therapy, the incidence of major adverse cardiovascular events (MACE) in patients with acute myocardial infarction (AMI) is still high. Risk factors such as diabetes, chronic kidney disease (CKD), atrial fibrillation, high coronary disease burden, low ejection fraction, and advanced age may worsen the prognosis of such patients [1][2][3]. SGLT2 inhibitors (SGLT2i) have been shown to improve cardiorenal endpoints in patients with type 2 diabetes (T2DM), CKD, and chronic heart failure with reduced ejection fraction (HFrEF) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%